(untitled) (Fiep Bulletin - online, 2015)
It is common knowledge that it is easier to walk downhill or down stairs then upwards, likewise that it is easier to lower a weight through a certain distance than to lift it the same vertical distance. In every day´s life both types of work exist and are equally common, but whereas a vast amount of research has been done in determining the cost of positive work, very few experiments have been done in order to evaluate the cost of performing negative work, or of determining the ratio (cost of positive work/cost of negative Work).